Sistemas de produção de porta-enxertos de seringueira - Guiducci, Erika Perches [UNESP] (2014)
Rubber trees are propagated by grafting method and its seeds used for obtaining the rootstocks. Environmental problems related to rootstocks development by the conventional system and the establishment of rules (Resolução SAA - 154/2013 of the São Paulo State) for production in suspended nurseries have motivated researches of new processes for rubber rootstocks production. The objective of this study was to evaluate rubber rootstocks production in suspended containers in a greenhouse and open skies. An experiment of seeding and another of development of rootstocks were conducted in Tanabi – SP/Brazil. The experiment of seeding compared the germination and vigor of rubber seeds among different seeding systems: conventional in soil beds, direct seeding on substrate in suspended containers in a greenhouse and at open skies. Emergence speed index and percentage of germination of seeds were evaluated in each seeding system. The results showed that the direct seeding system in the greenhouse is the most suitable for providing better seeds germination and adaptation to legislation, and that it is essential to use high vigor seeds. The experiment of development of rubber rootstocks evaluated the conventional production system under field conditions compared to greenhouse and open skies suspended containers systems. Diameter at five cm from colon, height, leaf area, root volume and dry weight of shoot and root system of the rootstocks were evaluated. It was concluded that, in the São Paulo Western Plateau region, the production of rubber rootstocks should be conducted in the greenhouse suspended containers system using an organic substrate